Faktor-Faktor Pada Mahasiswa Dalam Menumbuhkan Minat Berwirausaha - Ananda Zahrani Putri; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of creativity, self efficacy, and the use of social media partially and simultaneously. The population used in this study was students studying in Jakarta. Sampling with purposive sampling of 100 respondents. This research uses a quantitative research approach. Data collection techniques are done by distributing Microsoft Form help questionnaires on a likert scale from one to five. The data analysis technique used is using SmartPLS (Partial Least Square) software version 4.0.9.6. The results of the research concluded that: (1) creativity has a positive and significant influence on entrepreneurship interests; (2) self efficacy has a positively but not significantly influenced entrepreneurship interest; (3) the use of social media has a significant and positive influence upon entrepreneurship interest; and (4) creativity, self efficacy, and social media use jointly or simultaneously affect entreprenorial interests including moderate.